Experimental and analytical investigation on flexural behaviors of cast-in-place concrete-filled flexible composite tube beams. (25th April 2022) - Ran, Jinlin; Li, Tingchun; Shang, Liming; Jiang, Hua; Li, Weiteng; Zhang, Shilin
Highlights: A new cast-in-place construction method for FRCM-strengthened concrete is defined. The flexural behaviors of circular FRCM-strengthened beams are analyzed. The strength calculation model of circular FRCM-strengthened beams is proposed. Abstract: Fabric-reinforced cementitious matrix (FRCM) has become increasingly popular compared to other reinforcements materials of concrete; however, it is difficult but in urgent need to prepare FRCM-strengthened concrete members through a one-time cast-in-place construction procedure. Therefore, a novel system, i.e. concrete-filled flexible composite tube, is proposed, where the external tube is composed of geotextile mold and fabric mesh. While, this paper presents the results of a four-point bending test performed on five large-scale circular beams, and analyzed the influences of the number of layers of fabric meshes and the types of concrete substrate on the flexural behaviors. The test results indicate that the load–deflection responses are considerably improved by using more layers of fabric meshes, and can be further enhanced by adding the discrete fibers. Then, a comprehensive comparison with conventional FRCM-strengthened beams confirms that the full composite action of the concrete substrate and reinforcement layer was better achieved for the proposed system. Finally, a design model of concrete beams strengthened with FRCM on the entire circular cross section is proposed for the prediction on ultimate load, and shows a good agreement with the test results. The conclusions will pave the way for wider implementations of FRCM in practice.